The question of Tunisia’s status quo and the firman of 1871 - ATABAŞ, CEMAL (My University, 2023)
The status quo of Tunisia, that is, the nature of its relationship with the Ottoman centre emerged as a problem with the occupation of Algerian costs in 1830 and the centralisation of Tripoli in 1835. France frequently warned the Ottoman Empire not to subvert the status quo in Tunisia. Clarifying and internationally securing this formally undefined state of affairs had been the British policy in the region since the 1850s. Britain, especially with its consul, Richard Wood, endeavoured for a declaration of a firman stating that the Ottoman Empire recognised the inherited governorship of the Husaynid Dynasty and that the beys accepted the Sultan’s political suzerainty in Tunisia. This project, which was constantly delayed by the opposition of France, was realised in 1871. So the firman, which was expected to bring the region’s political position to wider international acceptance, was declared. This study aims to examine the debates about Tunisia’s status quo based on British and Ottoman archival sources. So, the efforts of the Ottoman Empire to protect the province, as well as the approaches and plans of Britain and France towards Tunisia, were explored.

Tunus’un statükosu yani Osmanlı merkezi ile irtibatının niteliği, Cezayir sahillerinin 1830’da işgali ve Trablusgarp’ın 1835’te merkeze bağlanması ile bir sorun olarak ortaya çıkmıştır. Fransa Osmanlı Devleti’ni bölgede statükonun bozulmaması konusunda sık sık uyarmıştır. Kapsamı tartışma konusu olan bu siyasi bağın içeriğini netleştirmek ve uluslararası güvenceye almak 1850’lerden itibaren İngiltere’nin Tunus politikasının ana eksenini oluşturmuştur. İngiltere, özellikle Tunus konsolosu Richard Wood’un gayretleriyle, Osmanlı Devleti’nin Hüseyni Âilesi’nin tevarüsen valilik hakkını tanıdığını ve beylerin de sultanın Tunus’taki siyasi egemenliğini kabul ettiklerini bildiren bir ferman çıkarılması için çalışmıştır. Fransa’nın engellemeleriyle sürekli olarak ertelenen bu proje 1871’de gerçekleştirilmiş ve bölgenin siyasi pozisyonunu daha geniş bir uluslararası kabule ulaştırması beklenen ferman ilan edilmiştir. Bu çalışma ile Tunus’un statükosu ile ilgili tartışmalar temelde İngiliz ve Osmanlı arşiv kaynakları ışığında incelenmiştir. Osmanlı Devleti’nin eyaleti koruma gayretleri, bunun yanında İngiltere’nin ve Fransa’nın bölgeye dair yaklaşımları ve planları açığa çıkarılmaya çalışılmıştır
Tunus’un Statükosu Sorunu ve 1871 Fermanı
Keywords: Sosyal ve Beşeri Bilimler; Tarih; Social Sciences and Humanities; History; Sanat ve Beşeri Bilimler (AHCI); Sanat ve Beşeri Bilimler; KÜLTÜREL ÇALIŞMALAR; TARİH; Arts & Humanities (AHCI); ARTS & HUMANITIES; CULTURAL STUDIES; HISTORY; Kültürel çalışmalar; Sosyal Bilimler ve Beşeri Bilimler; Cultural Studies; Social Sciences & Humanities; British Empire; France; North Africa; Ottoman Empire; Richard Wood; Tunisia; Tunus; Osmanlı Devleti; İngiltere; Fransa; Kuzey Afrika; Richard Wood; Tunisia; Ottoman Empire; British Empire; France; North Africa; Richard Wood